Intervenções urbanas a partir de investimentos do Programa de Aceleração do Crescimento (PAC) : a reterritorialização dos moradores do entorno da obra contorno norte de Maringá-PR - Oliveira, Adriano Aparecido de (2016)
In any case of urban intervention not only economic aspects should be taken into consideration, but the political, social, and cultural aspects of a region. Therefore, this research had as its objective to understand how the reterritorialization of residents from Hortência and Conjunto Thaís, in Maringá, Paraná happened after the construction of Contorno Norte begun. Thus, it was possible to discuss the impacts of the largest urban intervention in Maringá - consisting in the construction of Contorno Norte, which became feasible due to the Brazilian Growth Acceleration Program (PAC). This intervention is the construction of Contorno Norte. When analyzing the reterritorialization process of residents, it was necessary to understand the phases of territorialization and deterritorialization and how urban projects connected to the urban space production in Maringá (PR), understanding how the State capitalist logic works having the State as a legitimate agent. In this regard, this thesis discusses the concepts related to urban space production, territory, and urban entrepreneurialism, which are fledgling concepts in Administration field but which have been discussed by Organizational Studies researches, besides being part of many graduate programs in Administration. In order to make this research viable, a qualitative research with descriptive characteristics was carried out, the research involved documental research, bibliographic research and field research - this last one being done using semi-structured interviews with residents and one representative of public power - consequently, in order to analyse data collected the methodology chosen was content analysis. As results, this thesis demonstrates how the construction of Contorno Norte contributed to the comprehension of social- patial transformations in the region where it was built, besides the discussion of Territorialization, Deterritorialization, and Reterritorialization, especially of neighborhoods Hortência and Conjunto Thaís. When dealing with reterritorialization, conclusion was that residents do feel a considerable difference when considering the territory they lived in prior to the construction. Nowadays, residents report their feeling of exclusion regarding the rest of the urban population, and acknowledge a large amount of sociospatial problems that they understand as a direct reflection of the construction, which divided the city of Maringá (PR) and had a negative impact on people´s everyday life.